Does information and communication technology and financial development lead to environmental sustainability in India? An empirical insight. (July 2021) - Sahoo, Malayaranjan; Gupta, Mohini; Srivastava, Purwa
Highlights: This paper explores the relationship between ICT and CO2 emissions in India thorough ARDL approach. Electricity consumption has positively contributing CO2 emissions or reducing environmental sustainability in India. However, ICT has negative and significantly improving environmental sustainability and reducing emissions. Financial development and CO2 emissions negatively related. The results validate the Environmental Kuznets Curve's existence in India's case. Abstract: This paper examines the relationship between CO2 emissions, electricity consumption, financial development, Economic growth, Informational Communication Technology (ICT) from 1990 to 2018 in India. We have applied the structural break co-integration approach like Gregory Hansen approach to check long-term relations between the variables. ARDL bounds testing approach is used to know the long run and short-run elasticity. We find that electricity consumption is positively contributing CO2 emissions or reducing environmental sustainability in India. However, ICT has negative and significantly improving environmental sustainability or reducing emissions when measured in both ICT internet connection (ICTINT ) and ICT mobile Phones (ICTMOB ). Similarly, financial development and CO2 emissions are negatively related. The result indicates the existence of Environmental Kuznets Curve in India's case. Overall, environmental sustainability achieved in ICT and financial development sectors. Therefore govt. needs to focus more on the stringent policy in electricity production by investing more in the renewable energy sector to curb environmental degradation.